PEMBUATAN ARANG AKTIF DARI SABUT KELAPA SAWIT DENGAN BAHAN PENGAKTIF NH4HCO3 DAN (NH4)2C03 DOSIS RENDAH 1) - Gustan Pari; Ilah Sailah (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
This report deals with experimental study on the utilization of palm-tree bast as raw material for activated charcoal. In this regard, the main aim was to study the effect of concentrations of vaporized NH4HCO3and (NH4)2C03 solutions as activating agents (in persentages) on properties of activated charcoal, and to evaluate its use for purifying ground waler In this regard. the vapors might consist of NH3, CO2, and H2O. The manufacture of activated charcoal involved two consecutive stages, i.e. charcoaling and activation. The charcoaling was performed on the palm-tree bast in a retort equipped with electrical heater, followed by the activation stage where by the inside retort temperature was increased to 850ºC. At this temperature, the vapors of both NH4HCO3and (NH4)2C03 were each passed into the retort al several concentrations (i.e. 0.0 %; 0.01%; 0.025%; 0.075%. and 0.1% of either vapor) for 90 minutes at pressure of 0.05 kg/cm2 and on completion the resulting activated charcoal was examined of their inherent properties.It was found out that the activated charcoal with NH4HCO3vapor at 0.01% revealed the most satisfactory properties with respect to its selection for purifying the ground water. The yield of activated charcoal at this vapor percentage was 15.99%, moisture content 0.10%, ash content 31.85%, volatile matter 24.85%, carbon content 43.21%, adsorptive capacity of benzene 13.33 %, of CHCl3 16.28%, of NH3 26.65%. of CCl4 26.64%, of iodine 799.5 mg/g, of methylene blue 136.10 mg/g and surface area 463.41 m2/g. ·The ground water afler being purified with this selected activated charcoal revealed the improvement on its qualities. as shown by the decreases in Fe from 4.919 mg/l; to 0.00 mg/I, Zn from 0.031 mg/I to 0.00 mg/I, Mn from 7.780 mg/I to 6.16 mg/I; the increase in pH from 6.99 to 8.00 on and the more transparent in its color.